Laminate, optical article, lens, and glasses

By using a laminated body structure in the photochromic lens, using polyvinyl alcohol resin or cellulose resin as a base material, and combining resins such as epoxy resin as coatings, the problem of insufficient adhesion and shape stability in the prior art is solved, and better optical properties are achieved.

CN119604790APending Publication Date: 2025-03-11TOKUYAMA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380054156.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-29
Filing Date
2023-07-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, the adhesion and shape stability of the photochromic lenses are insufficient, which affects their application in optical articles.

Method used

A laminated body structure is adopted, including a first substrate and a second substrate, an adhesive layer and a coating. The first substrate and the second substrate contain polyvinyl alcohol resin or cellulose resin, the adhesive layer is between the two, the coating covers at least a part of the surface, and contains epoxy resin, urethane resin and acrylic resin.

Benefits of technology

The adhesion and shape stability of the laminated body and the optical element substrate are improved, and are suitable for the manufacturing of optical objects, lenses and glasses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604790A_ABST
    Figure CN119604790A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a laminate having excellent adhesion to an optical element substrate and excellent shape stability; and an optical article, a lens, and eyeglasses each comprising the laminate. According to one embodiment, a laminate may be provided. The laminate is provided with a first base material, a second base material, an adhesive layer, and a coating layer. The first base material and the second base material contain polyvinyl alcohol resin. The adhesive layer is interposed between the first substrate and the second substrate and adheres the first substrate and the second substrate to each other. The coating layer covers at least a portion of a surface of at least one of the first substrate and the second substrate, and contains a resin. The resin includes at least one selected from the group consisting of epoxy resins, urethane resins, and acrylic resins.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate, an optical article, a lens and glasses. Background Art

[0002] Plastic glasses are glasses that use plastic lenses as lenses. Plastic lenses can be manufactured, for example, by performing various processes on semi-finished lenses as semi-finished products. Functional layers such as hard coatings and anti-reflection films are provided on the convex surface of the semi-finished lenses. In addition, cutting and grinding are performed on the back of the concave surface of the semi-finished lenses.

[0003] In recent years, light-adjusting lenses with photochromic properties that change color according to the amount of ultraviolet light have attracted attention. Light-adjusting lenses can be obtained by adding photochromic compounds to plastic lenses. Photochromic compounds are compounds that can reversibly generate two or more isomers under the action of light, and the isomers have different absorption spectra.

[0004] As a method for producing a photochromic lens, conventionally used methods include a kneading method in which a photochromic compound is dispersed in a matrix of a semi-finished lens and a lamination method in which a layer containing a photochromic compound is provided on the surface of a semi-finished lens.

[0005] The adhesive sheet method is a method of manufacturing a semi-finished lens by integrating an adhesive sheet with a lens substrate, wherein the adhesive sheet is formed by sandwiching a resin layer containing a photochromic compound between two optical sheets. In this method, for example, an adhesive sheet is installed in a mold, and then a thermoplastic resin is injection-molded toward the adhesive sheet to obtain a semi-finished lens. If the adhesive sheet method is used, a self-supporting article containing a photochromic compound can be used to manufacture a semi-finished lens, so compared with the mixing method and the lamination method, there is a tendency to improve production efficiency and facilitate mass production.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2015 / 005391

[0009] Patent Document 2: International Publication No. 2019 / 163728

[0010] Patent Document 3: Japanese Patent Application No. 2011-501235 Summary of the invention

[0011] Problem that the invention aims to solve

[0012] An object of the present invention is to provide a laminate having excellent adhesion to an optical element substrate and excellent shape stability, and an optical article, a lens, and glasses including the laminate.

[0013] Solutions for solving problems

[0014] The present invention relates to a laminate. The laminate comprises: a first substrate and a second substrate, an adhesive layer, and a coating layer. The first substrate and the second substrate contain a polyvinyl alcohol resin or a cellulose resin. The adhesive layer is between the first substrate and the second substrate and bonds them. The coating layer covers at least a portion of the surface of at least one of the first substrate and the second substrate and contains a resin. The resin contains at least one selected from the group consisting of an epoxy resin, a urethane resin, and an acrylic resin.

[0015] Furthermore, the present invention relates to an optical article. The optical article includes the above-mentioned laminated body.

[0016] In addition, the present invention relates to a lens comprising the above optical article.

[0017] In addition, the present invention relates to a pair of spectacles comprising the above-mentioned lens.

[0018] Effects of the Invention

[0019] According to the present invention, there are provided a laminate having excellent adhesion to an optical element substrate and excellent shape stability, and an optical article, a lens, and glasses including the laminate. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a cross-sectional view schematically showing an example of a laminated body according to an embodiment.

[0021] Figure 2 This is a cross-sectional view schematically showing an example of the optical article according to the embodiment.

[0022] Figure 3 It is a perspective view schematically showing an example of glasses according to the embodiment. DETAILED DESCRIPTION

[0023] According to an embodiment, a laminate can be provided. The laminate comprises: a first substrate and a second substrate, an adhesive layer and a coating layer. The first substrate and the second substrate contain a polyvinyl alcohol resin or a cellulose resin. The adhesive layer is between the first substrate and the second substrate and bonds them. The coating layer covers at least a portion of the surface of at least one of the first substrate and the second substrate and contains a resin. The resin contains at least one selected from the group consisting of an epoxy resin, a urethane resin and an acrylic resin.

[0024] The laminated body of the embodiment is sometimes used as the above-mentioned adhesive sheet, for example, and is integrated with an optical element substrate such as a lens substrate. For the adhesive sheet using the first and second substrates containing polyvinyl alcohol resin or cellulose resin, for example, it can be integrated with a thermosetting resin by a casting polymerization method. The temperature of the thermosetting resin composition in the casting polymerization method is lower than the temperature of the thermoplastic resin composition for injection molding. Therefore, in optical articles based on the casting polymerization method, the adhesion between the adhesive sheet and the optical element substrate will be more reduced than the adhesion between the adhesive sheet and the optical element substrate in the optical article based on the injection molding method. In the laminated body of the embodiment, a coating is provided on the surface of at least one of the first and second substrates. The coating contains resins such as epoxy resins, urethane resins and acrylic resins, and therefore has better adhesion to the optical element substrate than the first and second substrates.

[0025] In addition, the adhesive sheet is sometimes subjected to shape processing such as bending to match the shape of the lens. Since the polyvinyl alcohol resin has a large number of hydroxyl groups on its surface, its film is easily affected by moisture in the air. Therefore, the adhesive sheet using a substrate containing polyvinyl alcohol resin tends to have low shape stability. The laminated body of the embodiment has a coating layer, so that it is possible to suppress the adhesion of moisture in the air to at least one of the first and second substrates. Therefore, the laminated body of the embodiment has excellent shape stability compared to a laminated body without a coating layer.

[0026] Hereinafter, the laminated body according to the embodiment will be described in detail.

[0027] [Laminated body]

[0028] As described above, the laminated body of the embodiment can be used as an adhesive sheet. In particular, the laminated body of the embodiment can be used as a functional sheet in which a functional dye such as a photochromic compound is blended in the adhesive layer.

[0029] The thickness of the laminate of the embodiment is preferably 100 μm or more, more preferably 150 μm or more, and further preferably 200 μm or more. If the thickness of the laminate is thick, there is a tendency for the shape stability to be improved. The upper limit of the thickness of the laminate is not particularly limited, and as an example, it is 1000 μm or less, and as another example, it is 500 μm or less.

[0030] Figure 1 It is a cross-sectional view schematically showing an example of a laminated body. Figure 1 The laminate 1 shown includes: a first substrate 2, a second substrate 3, an adhesive layer 4 interposed therebetween, a first coating 5 covering the first substrate 2, and a second coating 6 covering the second substrate 3. At least one of the first coating and the second coating may cover the side surface of the laminate 1. In this case, the first coating and the second coating may also be integrated.

[0031] <First and Second Substrates>

[0032] The first and second substrates (hereinafter, sometimes described as "substrates") include polyvinyl alcohol (PVA) resin or cellulose resin. The substrate may be composed of only PVA resin or cellulose resin, or may include other resins. As the cellulose resin, for example, acetyl cellulose such as triacetyl cellulose and diacetyl cellulose may be used, and propyl cellulose such as tripropyl cellulose and dipropyl cellulose may also be used. As other resins, polyvinyl formal, polyvinyl acetal, polyvinyl butyral, etc. modified with aldehydes may be cited.

[0033] The cellulose resin of the present invention can be used without particular limitation, but preferably has a visual light transmittance of higher than 92.5%.

[0034] The substrate may be any of unstretched, uniaxially stretched or biaxially stretched. The stretching direction may be any of the mechanical flow direction (MD) of the unstretched film, the direction (TD) orthogonal to the mechanical flow direction, and the direction obliquely intersecting the mechanical flow direction. Here, an unstretched sheet refers to a sheet in an unstretched state, and a uniaxially stretched sheet refers to a sheet formed by stretching an unstretched sheet in any of the above directions. A biaxially stretched sheet refers to a sheet formed by stretching in two directions in the above-mentioned stretching directions, and may be a biaxially stretched sheet that is stretched simultaneously, or a sequentially biaxially stretched sheet that is stretched in a specified direction and then stretched in other directions. In the case of a biaxially stretched sheet, it is generally preferred to stretch in the MD and TD directions. The stretching ratio is preferably 1.5 to 8 times.

[0035] The average degree of polymerization of the PVA resin is, for example, 100 to 10000, preferably 1500 to 8000, and more preferably 2000 to 5000. The average degree of polymerization of the PVA resin can be determined by a method in accordance with Japanese Industrial Standards (JIS) K6726:1994.

[0036] The PVA resin may contain boric acid. Boric acid is used as a crosslinking agent for crosslinking PVA with each other. The boric acid content of the PVA resin is, for example, 1% by mass or more and 20% by mass or less, preferably 3% by mass or more and 18% by mass or less, and more preferably 5% by mass or more and 15% by mass or less. The boric acid content can be calculated by inductively coupled plasma (IPC) luminescence analysis. Specifically, the substrate is first dissolved in an aqueous nitric acid solution to obtain a solution. The solution is used to perform IPC analysis to calculate the boron content. The boric acid content is converted from the boron content.

[0037] The substrate may be a polarizing film having polarization properties. When used as an adhesive sheet, at least one of the first and second substrates may be a polarizing film. The substrate having polarization properties preferably has a visual transmittance of 10% to 80% and a polarization degree of 30% to 99.9%.

[0038] The polarizing substrate includes a dichroic substance. The dichroic substance includes iodine and a dichroic dye. The dichroic dye may be an azo dye or an anthraquinone dye. Specific examples of dichroic dyes include direct red (CHLORANTINE FASTRED) (CI28160), Congo red (CI22120), Brilliant Blue B (CI24410), BENZOPURPURIN (CI23500), Chlorazol Black BH (CI22590), Direct Blue 2B (CI22610), Diamine Green (CI30295), Direct Yellow (CHRYSOPHENINE) (CI24895), Sirius Yellow (CI29000), Direct Fast Red (CI23630), Acid Black (CI20470), Direct Sky Blue (CI24400), Solophenyl Blue 4GL (CI34200), Direct Copper Blue 2B (CI24185), and Direct Violet (Nippon Brilliant Violet)BKconc(CI27885).

[0039] The thickness of the substrate is, for example, not less than 10 μm and not more than 100 μm. The thickness of the second substrate may be the same as or different from the thickness of the first substrate.

[0040] <Adhesive layer>

[0041] The adhesive layer may include at least one selected from the group consisting of polyurethane resin, polyurethane urea resin, polythiocarbamate resin and polythiocarbamate urea resin. The adhesive layer may include a functional pigment such as a photochromic compound. The adhesive layer may include a cured product of the adhesive composition described below.

[0042] The thickness of the adhesive layer is, for example, 0.1 μm or more and 100 μm or less. The thickness of the adhesive layer may be thinner or thicker than the thickness of the first and second substrates.

[0043] (Adhesive composition)

[0044] The adhesive composition includes a functional pigment and a polymer component. The polymer component becomes the matrix of the adhesive layer. The polymer component includes a second prepolymer, or a first polymer and a second prepolymer or a third prepolymer. In other words, the adhesive composition may include the following combinations: a first combination of a polymer component including a second prepolymer and a functional pigment; a second combination of a polymer component including a first polymer and a second prepolymer and a functional pigment; a third combination of a polymer component including a first polymer and a third prepolymer and a functional pigment; and a fourth combination of a polymer component including a first polymer, a second prepolymer and a third prepolymer and a functional pigment.

[0045] (Functional pigment)

[0046] The functional dye includes, for example, at least one selected from the group consisting of a photochromic compound, an ultraviolet absorber, a blue light absorber, an infrared absorber, and an electrochromic compound.

[0047] As the photochromic compound, for example, at least one selected from the group consisting of a benzopyran compound, a fulgide compound and a spirooxazine compound is used. As the photochromic compound, a benzopyran compound is preferably used. The benzopyran compound includes: a compound having a 1-benzopyran skeleton, a spiropyran compound including a spiropyran skeleton and a naphthopyran compound having a naphthopyran skeleton. The naphthopyran compound includes an indenonaphthopyran compound having an indenonaphthopyran skeleton. The benzopyran compound preferably includes an indenonaphthopyran compound having an indeno[2,1-f]naphtho[1,2-b]pyran skeleton. The cured product containing the benzopyran compound having an indeno[2,1-f]naphtho[1,2-b]pyran skeleton tends to have excellent durability.

[0048] The indenonaphthopyran compound preferably includes a compound represented by the following general formula (IIIa).

[0049]

[0050] In formula (IIIa), the Z ring is a substituted or unsubstituted spiro ring with the carbon atom at position 13 as a spiro atom. The Z ring can form an aliphatic ring together with the carbon atom at position 13, can form a condensed polycyclic ring, can form a heterocyclic ring, and can form a heterocyclic aromatic ring. The Z ring is preferably an aliphatic ring having 5 to 16 ring carbon atoms. The aliphatic ring further preferably has an alkyl group having 1 to 3 carbon atoms as a substituent.

[0051] In formula (IIIa), R 11 , R 12 , R 13 , R 14 , R 15 , R 16and R 17 Each of them is independently a hydrogen atom, a hydroxyl group, a methoxycarbonyl group, an ethoxycarbonyl group, an alkyl group, a cycloalkyl group, a haloalkyl group, an alkoxy group, an amino group, a substituted amino group, a heterocyclic group which may have a substituent, a halogen atom, an alkylthio group, an arylthio group which may have a substituent, a nitro group, a formyl group, a hydroxycarbonyl group, an alkylcarbonyl group, an alkoxycarbonyl group, an aralkyl group which may have a substituent, an aralkyloxy group which may have a substituent, an aryloxy group which may have a substituent, an aryl group which may have a substituent, a heteroaryl group which may have a substituent, a mercapto group, an alkoxyalkylthio group, a haloalkylthio group, a cycloalkylthio group which may have a substituent, or an oligomer group.

[0052] m is an integer of 0 to 4. When m is 2 to 4, a plurality of R 17 They may have the same structure as each other or different structures.

[0053] The number of carbon atoms in the alkyl group is preferably 1 to 10. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a tert-butyl group, a pentyl group, and a hexyl group.

[0054] The carbon number of the haloalkyl group is preferably 1 to 10. The haloalkyl group is preferably an alkyl group substituted with a fluorine atom, a chlorine atom or a bromine atom. Examples of suitable haloalkyl groups include trifluoromethyl, tetrafluoroethyl, chloromethyl, 2-chloroethyl and bromomethyl.

[0055] The number of ring carbon atoms in the cycloalkyl group is preferably 3 to 8. Examples of the cycloalkyl group include cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl. The cycloalkyl group may have a substituent, but the carbon number (3 to 8 carbon atoms) does not include the carbon number of the substituent.

[0056] The carbon number of the alkoxy group is preferably 1 to 10, more preferably 1 to 6. Examples of suitable alkoxy groups include methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, sec-butoxy and tert-butoxy.

[0057] The amino group is a primary amino group (-NH2). The substituted amino group is a secondary or tertiary amino group in which one or two hydrogen atoms are substituted. Examples of the substituents possessed by the substituted amino group include an alkyl group having 1 to 6 carbon atoms, a haloalkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 7 carbon atoms, an aryl group having 6 to 14 carbon atoms, and a heteroaryl group having 4 to 14 carbon atoms. Examples of suitable amino groups include amino, methylamino, dimethylamino, ethylamino, diethylamino, phenylamino, and diphenylamino.

[0058] The number of atoms in the heterocyclic group is preferably 3 to 10. The heterocyclic group may be an aliphatic heterocyclic group or an aromatic heterocyclic group. Specific examples of aliphatic heterocyclic groups include morpholinyl, piperidinyl, pyrrolidinyl, piperazinyl, and N-methylpiperazinyl. Specific examples of aromatic heterocyclic groups include indolinyl. The heterocyclic group may have a substituent. As a preferred substituent, an alkyl group having 1 to 10 carbon atoms may be listed. As suitable heterocyclic groups having a substituent, for example, 2,6-dimethylmorpholinyl, 2,6-dimethylpiperidinyl, and 2,2,6,6-tetramethylpiperidinyl may be listed.

[0059] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.

[0060] The number of carbon atoms in the alkylthio group is preferably 1 to 10. Examples of the alkylthio group include a methylthio group, an ethylthio group, an n-propylthio group, an isopropylthio group, an n-butylthio group, a sec-butylthio group, and a tert-butylthio group.

[0061] The carbon number of the arylthio group is preferably 6 to 10. Examples of the arylthio group include a phenylthio group, a 1-naphthylthio group, and a 2-naphthylthio group.

[0062] The number of carbon atoms in the alkylcarbonyl group is preferably 2 to 10. Examples of the alkylcarbonyl group include an acetyl group and an ethylcarbonyl group.

[0063] The number of carbon atoms in the alkoxycarbonyl group is preferably 2 to 10. Examples of the alkylcarbonyl group include a methoxycarbonyl group and an ethoxycarbonyl group.

[0064] The carbon number of the aralkyl group is preferably 7 to 11. Examples of the aralkyl group include a benzyl group, a phenethyl group, a phenylpropyl group, a phenylbutyl group, and a naphthylmethyl group.

[0065] The number of carbon atoms in the aralkyloxy group is preferably 7 to 11. Examples of the aralkyloxy group include a benzyloxy group and a naphthylmethoxy group.

[0066] The carbon number of the aryl group is preferably 6 to 12. Examples of the aryl group include a phenyl group, a 1-naphthyl group, and a 2-naphthyl group.

[0067] The number of carbon atoms in the aryloxy group is preferably 6 to 12. Examples of the aryloxy group include a phenoxy group and a naphthoxy group.

[0068] The number of carbon atoms in the heteroaryl group is preferably 3 to 12. Examples of the heteroaryl group include a thienyl group, a furyl group, a pyrrolinyl group, a pyridyl group, a benzothienyl group, a benzofuranyl group, and a benzopyrrolinyl group.

[0069] The carbon number of the alkoxyalkylthio group is preferably 2 to 10. Examples of the alkoxyalkylthio group include a methoxymethylthio group, a methoxyethylthio group, a methoxy-n-propylthio group, a methoxy-n-butylthio group, an ethoxyethylthio group, and a n-propoxypropylthio group.

[0070] The number of carbon atoms in the halogenoalkylthio group is preferably 1 to 10. Examples of the halogenoalkylthio group include a trifluoromethylthio group, a tetrafluoroethylthio group, a chloromethylthio group, a 2-chloroethylthio group, and a bromomethylthio group.

[0071] The number of carbon atoms in the cycloalkylthio group is preferably 3 to 8. Examples of the cycloalkylthio group include cyclopropylthio, cyclobutylthio, cyclopentylthio, and cyclohexylthio. The cycloalkylthio group may have a substituent, but the number of carbon atoms (3 to 8 carbon atoms) does not include the number of carbon atoms in the substituent.

[0072] The oligomer group comprises an oligomer chain, a linking group, and a terminal group.

[0073] The oligomer chain may include at least one selected from the group consisting of a polyalkylene oxide chain, a polysiloxane chain, and a polyester chain. The oligomer chain is a divalent group.

[0074] In the polyalkylene oxide chain, a linear or branched polyalkylene oxide having a carbon number of 1 to 10 is used as a repeating unit. The number of repetitions of the repeating unit is, for example, 3 to 1000. The repeating unit is, for example, -CH2O-, -CH2CH2O-, -CH(CH3)CH2O-, -CH2CH(CH3)O-, -CH2CH2CH2O-, or -CH2CH2C(CH3)O-.

[0075] In the polysiloxane chain, for example, a dimethylsilyleneoxy group (-Si(CH3)2O-) is used as a repeating unit. The number of repetitions of the repeating unit is, for example, 3 or more and 1,000 or less.

[0076] The polyester chain includes, for example, -OC(=O)CH2-, -OC(=O)CH2CH2CH2CH2C(=O)O-, or -OC(=O)CH2CH2CH2CH2C(=O)OCH2CH2-) as a repeating unit. The number of repetitions of the repeating unit is, for example, 3 or more and 1,000 or less.

[0077] The linking group bonds the photochromic compound to one end of the oligomer chain. Examples of the linking group include: -O-, -O-CH2CH2-O-, -O-CH2CH2-OC(=O)CH2CH2C(=O)-O-, or -O-CH2CH2-OC(=O)CH2CH2C(=O)-O-CH2-. The linking group may be a divalent group or a group having a valence of at least two.

[0078] The terminal group is bonded to the other end of the oligomer chain. The terminal group is, for example, a linear or branched alkyl group having 1 to 10 carbon atoms, a linear or branched alkoxy group having 1 to 10 carbon atoms, or a linear or branched alkenyl group having 2 to 30 carbon atoms. The terminal group is preferably a methyl group.

[0079] The oligomer group may include a first linking group, an oligomer chain and a second linking group. The first linking group and the second linking group may have the same structure as each other, or may have different structures from each other. The first linking group is connected to the first photochromic compound. The second linking group is connected to the second photochromic compound. The first photochromic compound and the second photochromic compound may have the same structure as each other, or may have different structures from each other.

[0080] The above-mentioned cycloalkyl group, arylthio group, aralkyl group, aralkyloxy group, aryloxy group, aryl group, heteroaryl group and cycloalkylthio group may be unsubstituted or may have a substituent.

[0081] The substituents that may be possessed by the cycloalkyl group, arylthio group, arylalkyl group, arylalkyloxy group, aryloxy group, aryl group, heteroaryl group and cycloalkylthio group may be selected from the group consisting of a primary amino group, a secondary amino group, a tertiary amino group, an alkyl group having 1 to 10 carbon atoms, a haloalkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a haloalkoxy group having 1 to 10 carbon atoms, an alkylthio group having 1 to 10 carbon atoms, a hydroxyl group, a cycloalkyl group having 3 to 8 carbon atoms, an aryl group having 6 to 12 carbon atoms, an alkylaryl group having 1 to 20 carbon atoms, a heterocycloalkyl group having 1 to 8 carbon atoms containing 1 to 5 heteroatoms, a heteroaryl group having 1 to 8 carbon atoms containing 1 to 5 heteroatoms, an aryloxy group having 6 to 12 carbon atoms, an arylthio group having 6 to 12 carbon atoms, a cyano group, a nitro group and a halogen atom. The number of the substituents may be one or two or more.

[0082] R 13 and R 14 , R 14 and R 15 , and R 15 and R 16 They may be bonded to each other to form an aliphatic ring having 2 to 5 carbon atoms, an aliphatic heterocyclic ring having 1 to 4 carbon atoms containing 1 to 3 heteroatoms, an aromatic ring having 4 to 12 carbon atoms, or an aromatic heterocyclic ring having 3 to 11 carbon atoms containing 1 to 6 heteroatoms. The aliphatic ring, aliphatic heterocyclic ring, aromatic ring, and aromatic heterocyclic ring may be unsubstituted or may have at least one substituent selected from the above substituent group.

[0083] The ultraviolet light absorber has an absorption wavelength in the ultraviolet (UV) region below 400nm. The ultraviolet light absorber may have a maximum absorption wavelength in a region above 330nm and below 380nm, or may have a maximum absorption wavelength in a region above 250nm and below 330nm. As the ultraviolet light absorber, an organic compound may be used. As the ultraviolet light absorber, for example, at least one selected from the group consisting of benzophenone derivatives, ethylhexyl methoxycinnamate, benzotriazole derivatives, and triazine derivatives may be used. The ultraviolet light absorber preferably includes at least one selected from the group consisting of benzophenone derivatives, ethylhexyl methoxycinnamate, and benzotriazole derivatives.

[0084] As the blue light absorber, a compound having an absorption spectrum in the wavelength region of higher than 400 nm and lower than 450 nm in the absorption spectrum can be used. Such a compound is, for example, at least one selected from the group consisting of perylene compounds, porphyrin compounds, carotenoid compounds, and cyanine compounds. As the blue light absorber, a porphyrin compound is preferably used, and a tetraazaporphyrin compound is more preferably used.

[0085] The high-energy visible light absorber is a blue light absorber having an absorption peak in a wavelength region of 400 nm to 420 nm. As the high-energy visible light absorber, the same as the blue light absorber can be used.

[0086] The dye is preferably included in the compound having an absorption peak in the wavelength region of more than 540nm and less than 650nm in the absorption spectrum, and more preferably included in the compound having an absorption peak in the wavelength region of more than 550nm and less than 600nm. If such a compound is included, the anti-glare property of the optical article can be improved. As such a compound, nitro compounds, azo compounds, anthraquinone compounds, threne compounds, porphyrin compounds, rare earth metal compounds, etc. can be listed. As such a compound, at least one selected from the group consisting of tetraazaporphyrin compounds and neodymium compounds is preferably used.

[0087] Examples of the electrochromic compound include organic substances such as viologen, polymers having electrochromic properties, and metal salt complexes having d atoms.

[0088] The ratio of the functional dye in the solid content of the adhesive composition is, for example, 0.1 mass % to 10 mass %, or preferably 1 mass % to 5 mass %.

[0089] (Second prepolymer)

[0090] The second prepolymer can be obtained by reacting the first prepolymer with a second multifunctional active hydrogen compound as a chain extender, and the first prepolymer is obtained by reacting the first multifunctional active hydrogen compound with the first iso(thio)cyanate compound. The second prepolymer has more than two iso(thio)cyanate groups. The second prepolymer preferably has iso(thio)cyanate groups at both ends of the main chain. The second prepolymer includes at least one selected from the group consisting of carbamate prepolymers, urea prepolymers, carbamate urea prepolymers, thiocarbamate prepolymers, thiourea prepolymers and thiocarbamate urea prepolymers. The second prepolymer is chemically bonded to the hydroxyl groups on the surface of the first and second substrates with water in the atmosphere to generate at least one selected from the group consisting of (thio)carbamate resins, (thio)urea resins and (thio)carbamate urea resins.

[0091] The number average molecular weight of the second prepolymer is preferably more than 5000, more preferably more than 10000, and further preferably more than 13000. If the second prepolymer with a large number average molecular weight is used, the peel strength of the laminate tends to improve. That is, it is believed that the second prepolymer with a large number average molecular weight is easily entangled with each other, so the cohesive force improves, and thus the adhesive force improves.

[0092] The number average molecular weight of the second prepolymer is preferably 50000 or less, more preferably 40000 or less, and further preferably 30000 or less. If the number average molecular weight of the second prepolymer is too large, the peel strength of the laminate tends to decrease. That is, the amount of iso(thio)cyanate groups contained in the per unit mass of the second prepolymer with a large number average molecular weight is small, so there is a tendency for the adhesive force to weaken.

[0093] The number average molecular weight of the second prepolymer can be measured by gel permeation chromatography (GPC). When measuring, the measurement is carried out under the following conditions: chromatographic column: two Shodex KD-806M (manufactured by Showa Denko K.K.) connected in series; eluent: LiBr (10 mmol / L) / DMF solution; flow rate: 1 mL / min; detector: RI detector; second prepolymer sample solution: 1.0% dimethylformamide (DMF) solution. As analysis software, the GPC analysis software "Empower Personal GPC Option" manufactured by Nihon Waters KK is used.

[0094] The softening point of the second prepolymer is preferably 90° C. or higher, more preferably 100° C. or higher, and further preferably 110° C. or higher. If the softening point of the second prepolymer is high, there is a tendency that the heat resistance of the laminate is improved and the adhesion is further improved. The upper limit of the softening point of the second prepolymer is not particularly limited, and as an example, it can be 200° C. or lower, and as another example, it can be 160° C. or lower.

[0095] The softening point of the second prepolymer is measured, for example, by the following method. First, the second prepolymer is dissolved in an organic solvent to obtain a solution. The concentration of the second prepolymer in the solution is, for example, set to 34% by mass. The solution is poured into a stainless steel container and dried at 40°C for 10 hours, 60°C for 10 hours, and then at 60°C for 12 hours in a vacuum dryer to prepare a test piece with a thickness of 1 mm. The obtained test piece is analyzed using a thermomechanical measuring device (manufactured by Seiko Instruments Co., Ltd., TMA120C) to obtain the softening point. For the measurement conditions, the heating rate is set to 10°C / min, the measurement temperature range is set to 30-200°C, and a needle probe with a front end diameter of 0.5 mm is used.

[0096] In the solid content of the adhesive composition, the second prepolymer may occupy the main component. In the solid content of the adhesive composition, the proportion of the second prepolymer is, for example, 90% by mass or more and 99% by mass or less. It should be noted that when the adhesive composition is a second or fourth combination of a polymer component comprising a first polymer and a second prepolymer and a photochromic compound, in the solid content of the adhesive composition, the proportion of the second prepolymer is, for example, 5% by mass or more and 50% by mass or less, preferably 10% by mass or more and 40% by mass or less.

[0097] (First prepolymer)

[0098] The first prepolymer can be obtained by reacting the first multifunctional active hydrogen compound with the first iso(thio)cyanate compound. The first prepolymer has two or more iso(thio)cyanate groups. The first prepolymer preferably has iso(thio)cyanate groups at both ends of the main chain. The first prepolymer includes at least one selected from the group consisting of carbamate prepolymers, urea prepolymers, thiocarbamate prepolymers and thiourea prepolymers. The first prepolymer becomes the raw material of the second prepolymer.

[0099] The number average molecular weight of the first prepolymer is preferably 500 to 10000, and more preferably 1000 to 5000. The number average molecular weight of the first prepolymer can be measured by the same method as that of the second prepolymer.

[0100] (First iso(thio)cyanate compound)

[0101] The first iso(thio)cyanate compound has two or more iso(thio)cyanate groups. The first iso(thio)cyanate compound preferably has two iso(thio)cyanate groups. The first iso(thio)cyanate compound is more preferably a diisocyanate compound containing two iso(thio)cyanate groups.

[0102] The molar mass of the first iso(thio)cyanate compound is preferably 100 to 500. If the first iso(thio)cyanate compound is used within this range, a second prepolymer and a first polymer having a desired number average molecular weight are likely to be obtained. The molar mass of the first iso(thio)cyanate compound is more preferably 150 to 300.

[0103] The first iso(thio)cyanate compound comprises at least one selected from the group consisting of an aliphatic iso(thio)cyanate compound, an alicyclic iso(thio)cyanate compound, and an aromatic iso(thio)cyanate compound. The first iso(thio)cyanate compound is preferably an alicyclic iso(thio)cyanate compound. A single type may be used as the first iso(thio)cyanate compound, or a plurality of types may be mixed and used.

[0104] Examples of the aliphatic isocyanate compound include pentamethylene diisocyanate, hexamethylene diisocyanate, heptamethylene diisocyanate, octamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, and 1,2-bis(2-isocyanatoethylthio)ethane.

[0105] Examples of the alicyclic isocyanate compound include isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, dicyclohexylmethane-4,4′-diisocyanate (hydrogenated diphenylmethane diisocyanate), norbornane diisocyanate, 2,5-bis(isocyanatomethyl)-bicyclo[2,2,1]-heptane, and 2,6-bis(isocyanatomethyl)-bicyclo[2,2,1]-heptane.

[0106] Examples of the aromatic isocyanate compound include xylylene diisocyanate (o-, m-, and p-), toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, and 4,4′-diphenylmethane diisocyanate.

[0107] Examples of aliphatic isothiocyanate compounds include hexamethylene diisothiocyanate, 1,2-diisothiocyanatoethane, 1,3-diisothiocyanatopropane, 1,4-diisothiocyanatobutane, 1,6-diisothiocyanatohexane, 2,4,4-trimethylhexamethylene diisothiocyanate, thiobis(3-isothiocyanatopropane), thiobis(2-isothiocyanatoethane), and dithiobis(2-isothiocyanatoethane).

[0108] Examples of the alicyclic isothiocyanate compound include isophorone diisothiocyanate, cyclohexane diisothiocyanate, 2,4-bis(isothiocyanatomethyl)norbornane, 2,5-bis(isothiocyanatomethyl)norbornane, 2,6-bis(isothiocyanatomethyl)norbornane, 3,5-bis(isothiocyanatomethyl)norbornane, and norbornane diisocyanate.

[0109] Examples of the aromatic isothiocyanate compound include p-phenylenediisopropylidene diisocyanate, 1,2-phenylene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-diisothiocyanatotoluene, xylylene diisocyanate (o-, m-, p-), 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1,1′-methylenebis(4-isothiocyanatobenzene), 1,1′-methylenebis(4-isothiocyanato-2-methylbenzene), and 1,1′-methylenebis(4-isothiocyanato-3-methylbenzene).

[0110] (First polyfunctional active hydrogen compound)

[0111] The first multifunctional active hydrogen compound has two or more active hydrogen groups. The first multifunctional active hydrogen compound preferably has two active hydrogen groups. The active hydrogen group includes at least one selected from the group consisting of a hydroxyl group, an amino group, a carboxyl group, and a thiol group. The first multifunctional active hydrogen compound, for example, includes at least one selected from the group consisting of a polyol compound containing two or more hydroxyl groups, a polyamine compound containing two or more amino groups, a dicarboxylic acid containing two carboxyl groups, and a polythiol compound containing two or more thiol groups. As the first multifunctional active hydrogen compound, a single type may be used, or a plurality of types may be mixed and used.

[0112] The first multifunctional active hydrogen compound preferably comprises a polyol compound. If a polyol compound is used, a first prepolymer having a (thio)urethane bond can be obtained. The repeating structure of the polyol compound helps to provide a matrix in the adhesive layer that is not easy to hinder the structural change of the photochromic compound. If a polyol compound is used, there is a tendency for the photochromic property of the laminate to be improved.

[0113] The number average molecular weight of the polyol compound is preferably 500 or more and 3000 or less. If a polyol having a number average molecular weight within this range is used, there is a tendency to obtain a second prepolymer and a first polymer having a desired number average molecular weight. The number average molecular weight of the polyol compound is more preferably 800 or more and 2000 or less.

[0114] The polyol compound may include at least one selected from the group consisting of polyether polyol, polyester polyol, polycarbonate polyol and polycaprolactone polyol. The polyol compound preferably includes polycarbonate polyol. If polycarbonate polyol is used, the adhesion of the laminate tends to be improved.

[0115] The polycarbonate polyol can be obtained, for example, by the monophosgenation of low molecular weight polyols or the transesterification method of ethylene carbonate, diethyl carbonate, diphenyl carbonate, or the like. Examples of the low molecular weight polyol include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 3-methyl-1,5-pentanediol, 2-ethyl-4-butyl-1,3-propanediol, diethylene glycol, dipropylene glycol, neopentyl glycol, cyclohexane-1,4-diol, cyclohexane-1,4-dimethanol, dimer acid diol, ethylene oxide and propylene oxide adducts of bisphenol A, bis(β-hydroxyethyl)benzene, xylene glycol, glycerol, trimethylolpropane, and pentaerythritol.

[0116] As the polycarbonate polyol, the “DURANOL (registered trademark)” series manufactured by Asahi Kasei Corporation, the “KURARAY POLYOL (registered trademark)” series manufactured by Kuraray Co., Ltd., the “PLACCEL (registered trademark)” series manufactured by Daicel Corporation, the “NIPPOLLAN (registered trademark)” series manufactured by Tosoh Corporation, the “ETERNACOLL (registered trademark)” series manufactured by UBE Corporation, etc. can be used.

[0117] The polycaprolactone polyol can be obtained, for example, by ring-opening polymerization of ε-caprolactone. As the polycaprolactone polyol, the "PLACCEL (registered trademark)" series manufactured by Daicel Corporation and the like can be used.

[0118] The polyether polyol can be obtained, for example, by reacting a compound having two or more active hydrogen groups in the molecule with an alkylene oxide. Examples of the compound having two or more active hydrogen groups in the molecule include water, ethylene glycol, propylene glycol, butylene glycol, glycerol, trimethylolpropane, hexanetriol, triethanolamine, diglycerol, pentaerythritol, trimethylolpropane, hexanetriol, etc. Examples of the alkylene oxide include cyclic ether compounds such as ethylene oxide, propylene oxide, and tetrahydrofuran.

[0119] Examples of the polyether polyol include “EXCENOL (registered trademark)” series and “EMULSTAR (registered trademark)” series manufactured by AGC Corporation, and “ADEKA Polyether” series manufactured by ADEKA Corporation.

[0120] Polyester polyols can be obtained, for example, by condensation reaction of polyols and polyacids. Examples of polyols include ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 3,3'-dimethylolheptane, 1,4-cyclohexanedimethanol, neopentyl glycol, 3,3-bis(hydroxymethyl)heptane, diethylene glycol, dipropylene glycol, glycerol, trimethylolpropane, etc. Examples of polyacids include succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, cyclopentanedicarboxylic acid, cyclohexanedicarboxylic acid, phthalic acid, isophthalic acid, terephthalic acid, naphthalene dicarboxylic acid, etc.

[0121] As the polyester polyol, “POLYLITE (registered trademark)” series manufactured by DIC Corporation, “NIPPOLLAN (registered trademark)” series manufactured by Tosoh Corporation, “MAXIMOL (registered trademark)” series manufactured by AIR WATER PERFORMANCE CHEMICAL INC., and the like can be used.

[0122] The polythiol compound may include at least one selected from the group consisting of aliphatic polythiol, aromatic polythiol, and polythiol containing a sulfur atom in addition to a mercapto group.

[0123] Examples of aliphatic polythiols include methanedithiol, 1,2-ethanedithiol, 1,1-propanedithiol, 1,2-propanedithiol, 1,3-propanedithiol, 2,2-propanedithiol, 1,6-hexanedithiol, 1,2,3-propanetriol, tetrakis(mercaptomethyl)methane, 1,1-cyclohexanedithiol, 1,2-cyclohexanedithiol, 2,2-dimethylpropane-1,3-dithiol, 3,4-dimethoxybutane-1,2-dithiol, 2-methylcyclohexane-2,3-dithiol, 1 ,1-bis(mercaptomethyl)cyclohexane, bis(2-mercaptoethyl)thiomalate, 2,3-dimercaptosuccinic acid (2-mercaptoethyl ester), 2,3-dimercapto-1-propanol (2-mercaptoacetate), 2,3-dimercapto-1-propanol (3-mercaptoacetate), diethylene glycol bis(2-mercaptoacetate), diethylene glycol bis(3-mercaptopropionate), 1,2-dimercaptopropyl methyl ether, 2,3-dimercaptopropyl methyl ether, 2,2-bis(mercaptomethyl)-1,3-propanedithiol, etc.

[0124] Examples of aromatic polythiols include 1,2-dimercaptobenzene, 1,3-dimercaptobenzene, 1,4-dimercaptobenzene, 1,2-di(mercaptomethyl)benzene, 1,3-di(mercaptomethyl)benzene, 1,4-di(mercaptomethyl)benzene, 1,3-di(mercaptoethyl)benzene, 1,4-di(mercaptoethyl)benzene, 1,2-di(mercaptomethoxy)benzene, 1,3-di(mercaptomethoxy)benzene, 1,4-di(mercaptomethoxy)benzene, 1,2-di(mercaptoethoxy)benzene, 1,3-di(mercaptoethoxy)benzene, 1,4-di(mercaptoethoxy)benzene, 1,2,3-trimercaptobenzene, 1,2,4-trimercaptobenzene, 1,3,5-trimercaptobenzene, 1,2,3-tri(mercaptomethyl)benzene, 1,2,4-tris(mercaptomethyl)benzene, 1,3,5-tris(mercaptomethyl)benzene, 1,2,3-tris(mercaptoethyl)benzene, 1,2,4-tris(mercaptoethyl)benzene, 1,3,5-tris(mercaptoethyl)benzene, 1,2,3-tris(mercaptomethoxy)benzene, 1,2,4-tris(mercaptomethoxy)benzene, 1,3,5-tris(mercaptomethoxy)benzene, 1,2,3-tris(mercaptoethoxy)benzene, 1,2,4-tris(mercaptoethoxy)benzene, 1,3,5-tris(mercaptoethoxy)benzene, 1,2,3,4-tetramercaptobenzene, 1,2,3,5-tetramercaptobenzene, 1,2,4,5-tetramercaptobenzene, 1,2,3,4-tetra(mercaptomethyl)benzene, and the like.

[0125] Examples of polythiols containing sulfur atoms in addition to mercapto groups include bis(mercaptomethyl)sulfide, bis(mercaptoethyl)sulfide, bis(mercaptopropyl)sulfide, bis(mercaptomethylthio)methane, bis(2-mercaptoethylthio)methane, bis(3-mercaptopropylthio)methane, 1,2-bis(mercaptomethylthio)ethane, 1,2-bis(2-mercaptoethylthio)ethane, 1,2-bis(3-mercaptopropylthio)methane, 1,3-bis(mercaptomethylthio)propane, 1,3-bis(2-mercaptoethylthio)propane, 1,3-bis(3-mercaptopropylthio)propane, 1,2-bis(2-mercaptoethylthio)-3-mercaptopropane, 2-mercaptoethylthio-1,3-propanedithiol, 1,2,3-tris(mercaptomethylthio)propane, 1,2,3-tris(2-mercaptoethylthio)propane, and the like.

[0126] The amount of the first multifunctional active hydrogen compound is preferably adjusted in such a manner that the ratio M11 / M12 of the molar amount M11 of the active hydrogen group contained in the first multifunctional active hydrogen compound and the molar amount M12 of the iso(thio)cyanate group contained in the first iso(thio)cyanate compound is greater than or equal to 0.30 and less than or equal to 0.90. If the ratio M11 / M12 is within the above range, a sufficient amount of at least one of the urethane bond and the urea bond can be formed in the first prepolymer, and a soft adhesive layer that does not easily hinder the structural change of the photochromic compound can be formed. The ratio M11 / M12 is preferably greater than or equal to 0.40 and less than or equal to 0.850, and more preferably greater than or equal to 0.50 and less than or equal to 0.80.

[0127] The ratio S1 / S2 of the mass S1 of the first polyfunctional active hydrogen compound to the mass S2 of the first iso(thio)cyanate compound is preferably 0.1 or more and 10 or less. If the ratio S1 / S2 is within the above range, a second prepolymer having a sufficient amount of isocyanate groups per unit mass can be obtained. The ratio S1 / S2 is preferably 0.8 or more and 5 or less, and more preferably 1 or more and 4 or less.

[0128] (Second polyfunctional active hydrogen compound)

[0129] The second multifunctional active hydrogen compound has two or more active hydrogen groups. The second multifunctional active hydrogen compound reacts with the first prepolymer to generate a second prepolymer. The second multifunctional active hydrogen compound acts as a chain extender for connecting the first prepolymers. The second multifunctional active hydrogen compound preferably has two active hydrogen groups. As the second multifunctional active hydrogen compound, the compounds listed in the first multifunctional active hydrogen compound can be used.

[0130] The second multifunctional active hydrogen compound preferably comprises a polyamine. If a polyamine is used, a second prepolymer having a (thio)urethane urea bond can be obtained. If such a second prepolymer is used, there is a tendency for the adhesion of the laminate to be improved. The molar mass of the polyamine is preferably 50 or more and 500 or less. If a polyamine having a molar mass within this range is used, there is a tendency for a second prepolymer having a desired number average molecular weight to be obtained. The molar mass of the polyamine is more preferably 50 or more and 300 or less. The polyamine comprises a diamine and a triamine, preferably a diamine.

[0131] Examples of the polyamine include isophoronediamine, ethylenediamine, 1,2-diaminopropane, 1,3-diaminopropane, 1,2-diaminobutane, 1,3-diaminobutane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, piperazine, N,N-bis-(2-aminoethyl)piperazine, bis-(4-aminocyclohexyl)methane, bis-(4-amino-3-butylcyclohexyl)methane, Methane, 1,2-, 1,3- and 1,4-diaminocyclohexane, norbornanediamine, hydrazine, adipic acid dihydrazide, phenylenediamine, 4,4'-diphenylmethanediamine, N,N'-diethylethylenediamine, N,N'-dimethylethylenediamine, N,N'-dipropylethylenediamine, N,N'-dibutylethylenediamine, N-methylethylenediamine, N-ethylethylenediamine, bis(hexylene)triamine, 1,2,5-pentanetriamine, etc.

[0132] The polyamine preferably contains at least one selected from the group consisting of isophoronediamine, ethylenediamine, bis-(4-aminocyclohexyl)methane, and 1,6-diaminohexane.

[0133] The amount of the second polyfunctional active hydrogen compound is preferably adjusted so that the ratio M13 / M14 of the molar amount M13 of the active hydrogen group contained in the second polyfunctional active hydrogen compound to the molar amount M14 of the iso(thio)cyanate group contained in the first prepolymer is 0.21 or more and 0.9 or less. If the ratio M13 / M14 is within the above range, a sufficient amount of the second prepolymer can be generated.

[0134] The ratio S3 / S4 of the mass S3 of the second polyfunctional active hydrogen compound to the mass S4 of the first prepolymer is preferably 0.01 or more and 0.5 or less. If the ratio S3 / S4 is within the above range, a second prepolymer having a sufficient amount of isocyanate groups per unit mass can be obtained. The ratio S3 / S4 is more preferably 0.05 or more and 0.3 or less.

[0135] (First polymer)

[0136] The first polymer can be obtained by reacting the second prepolymer with a monofunctional active hydrogen compound having one active hydrogen group. Typically, the first polymer does not have an iso(thio)cyanate group. The end of the first polymer is modified with a non-reactive functional group. The first polymer comprises at least one selected from the group consisting of a carbamate polymer, a urea polymer, a carbamate urea polymer, a thiocarbamate polymer, a thiourea polymer, and a thiocarbamate urea polymer.

[0137] The first polymer chemically bonds with the second prepolymer and / or the third prepolymer and the hydroxyl groups on the surfaces of the first and second substrates at a high temperature to generate at least one selected from the group consisting of (thio)urethane resins, (thio)urea resins and (thio)urethane urea resins.

[0138] The number average molecular weight of the first polymer is preferably more than 5000, more preferably more than 10000, and more preferably more than 13000. If a first polymer with a large number average molecular weight is used, there is a tendency that the peel strength of the laminate is improved. The number average molecular weight of the first polymer is preferably less than 50000, more preferably less than 40000, and more preferably less than 30000. If the number average molecular weight of the first polymer is too large, there is a tendency that the peel strength of the laminate is reduced. The number average molecular weight can be measured by the same method as the second prepolymer.

[0139] The softening point of the first polymer is preferably 90°C or more, more preferably 100°C or more, and further preferably 110°C or more. If the softening point of the first polymer is high, there is a tendency that the heat resistance of the laminate is improved and the adhesion is further improved. The upper limit of the softening point of the first polymer is not particularly limited, and as an example, it can be 200°C or less, and as another example, it can be 160°C or less. The softening point of the mixture can be measured by the same method as the second prepolymer.

[0140] The first polymer may exist in the form of a mixture with the second prepolymer. The mixture of the first polymer and the second prepolymer can be obtained by adjusting the amount of the monofunctional active hydrogen compound. That is, the ratio M5 / M6 of the molar amount M6 of the iso(thio)cyanate group contained in the second prepolymer to the molar amount M5 of the active hydrogen group contained in the monofunctional active hydrogen compound is adjusted to be less than 1, thereby generating a mixture of the second prepolymer and the first polymer, wherein the iso(thio)cyanate group of the second prepolymer is protected with a monofunctional active hydrogen compound. The ratio M5 / M6 is preferably greater than 0.75 and less than 0.95.

[0141] The number average molecular weight of the mixture is preferably more than 5000, more preferably more than 10000, and further preferably more than 13000. If a mixture with a large number average molecular weight is used, there is a tendency that the peel strength of the laminate is improved. The number average molecular weight of the mixture is preferably less than 50000, more preferably less than 40000, and further preferably less than 30000. If the number average molecular weight of the mixture is too large, there is a tendency that the peel strength of the laminate is reduced. The number average molecular weight can be measured by the same method as the second prepolymer.

[0142] The softening point of the mixture is preferably 90° C. or more, more preferably 100° C. or more, and further preferably 110° C. or more. If the softening point of the mixture is high, the heat resistance of the laminate is improved and the adhesion is further improved. The upper limit of the softening point of the mixture is not particularly limited, and as an example, it can be 200° C. or less, and as another example, it can be 160° C. or less. The softening point of the mixture can be measured by the same method as the second prepolymer.

[0143] The ratio of the first polymer in the solid content of the adhesive composition is, for example, 75 mass % or more and 95 mass % or less.

[0144] The mixture of the first polymer and the second prepolymer may include a fourth prepolymer. The fourth prepolymer is a compound in which a portion of the iso(thio)cyanate groups of the second prepolymer are protected by a monofunctional active hydrogen compound and the remaining portion is not protected. The fourth prepolymer may include one iso(thio)cyanate group and one monofunctional active hydrogen compound protecting group. The fourth prepolymer has an iso(thio)cyanate group, and thus improves the adhesion of the laminate in the same manner as the second prepolymer.

[0145] In the mixture of the first polymer, the second prepolymer and the fourth prepolymer, the proportion of the first polymer is, as an example, 1% by mass or more and 40% by mass or less, and as another example, 10% by mass or more and 30% by mass or less. In the above mixture, the proportion of the second prepolymer is, as an example, 1% by mass or more and 40% by mass or less, and as another example, 10% by mass or more and 30% by mass or less. In the above mixture, the proportion of the fourth prepolymer is, as an example, 1% by mass or more and 80% by mass or less, and as another example, 40% by mass or more and 80% by mass or less.

[0146] The adhesive layer may be a cured product of an adhesive composition containing the first polymer, the second prepolymer, and the fourth prepolymer, or may be a cured product of an adhesive composition containing the first polymer and the fourth prepolymer.

[0147] (Monofunctional active hydrogen compound)

[0148] The monofunctional active hydrogen compound has one active hydrogen group. The monofunctional active hydrogen reacts with the iso(thio)cyanate group of the second prepolymer to generate the first polymer, thereby stopping further reaction. The active hydrogen group includes at least one selected from the group consisting of a hydroxyl group, an amino group, a carboxyl group, and a mercapto group.

[0149] The monofunctional active hydrogen compound includes, for example, at least one selected from the group consisting of a monoalcohol compound containing one hydroxyl group, a monoamine compound containing one amino group, a carboxylic acid containing one carboxyl group, and a monothiol compound containing one mercapto group. The monofunctional active hydrogen compound may be used alone or in combination of two or more.

[0150] The monofunctional active hydrogen compound is preferably a monoamine compound. When a monoamine compound is used, a first polymer having a (thio)urea bond can be obtained.

[0151] The monofunctional active hydrogen compound preferably contains an amine having a 2,2,6,6-pentamethyl-4-piperidinyl moiety as shown in the following general formula (3). The amine having a 2,2,6,6-pentamethyl-4-piperidinyl moiety can function as a hindered amine, thereby improving the light stability of the laminate.

[0152]

[0153] In the general formula (3), R 21 is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. 22 is an alkylene group having 1 to 3 carbon atoms. a is 0 or 1.

[0154] The monofunctional active hydrogen compound is preferably R 21 1,2,2,6,6-pentamethyl-4-aminopiperidine wherein a is 0 and is methyl.

[0155] The ratio S5 / S6 of the mass S5 of the monofunctional active hydrogen compound to the mass S6 of the second prepolymer is preferably 0.001 or more and 0.100 or less. If the ratio S5 / S6 is within the above range, a first polymer having a sufficient amount of isocyanate groups per unit mass can be obtained. The ratio S5 / S6 is more preferably 0.010 or more and 0.030 or less.

[0156] (Third prepolymer)

[0157] The third prepolymer is a compound having two or more iso(thio)cyanate groups obtained by reacting the first multifunctional active hydrogen compound with the first iso(thio)cyanate compound. That is, the third prepolymer is the same compound as the first prepolymer. The third prepolymer chemically bonds with the hydroxyl groups on the surface of the first prepolymer and the first and second substrates at high temperature to generate at least one selected from the group consisting of (thio)urethane resin, (thio)urea resin and (thio)urethane urea resin.

[0158] When the adhesive composition is the third combination or the fourth combination of the polymer component including the first polymer and the third prepolymer and the photochromic compound, the proportion of the third prepolymer in the solid content of the adhesive composition is, for example, 5 mass % to 20 mass %.

[0159] (additive)

[0160] The adhesive composition may contain an additive, such as at least one selected from the group consisting of a polymerization catalyst, a polymerization initiator, an antistatic agent, an internal mold release agent, an antioxidant, a light stabilizer, an anti-coloring agent, a fluorescent dye, a dye, a pigment, a fragrance, a solvent, a leveling agent, and a resin modifier. The adhesive composition preferably contains at least one of an antioxidant and a leveling agent.

[0161] As antioxidants, the following can be used: 2,6-di-tert-butyl-4-methylphenol; IRGANOX 245 manufactured by BASF Japan Ltd.: ethylenebis(oxyethylene)bis[3,5-tert-butyl-4-hydroxy-m-tolyl]propionate]; IRGANOX 1076 manufactured by BASF Japan Ltd.: octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; IRGANOX 1010 manufactured by BASF Japan Ltd.: pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; IRGANOX 1035, 1075, 104, 3790, 5057, 565 manufactured by BASF Japan Ltd., etc.

[0162] As the leveling agent, silicone surfactants, fluorine-containing surfactants, etc. can be used. Specifically, L-7001, L-7002, L-7604, FZ-2123 manufactured by Dow Toray Co., Ltd.; Megaphac F-470, Megaphac F-1405, Megaphac F-479 manufactured by DIC Corporation; Flowlator FC-430 manufactured by 3M Japan Co., Ltd., etc. can be used.

[0163] As the light stabilizer, it is preferred to use a hindered amine compound having a 2,2,6,6-tetramethyl-4-piperidyl skeleton, and commercially available products can be used. Examples thereof include bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, 1-[2-{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy}ethyl]-4-{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy}-2,2,6,6-tetramethylpiperidine, 4-benzoyloxy-2,2,6,6-tetramethylpiperidine, methyl(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, dicarboxylic acid ester, 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate, 2-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]-2-butylmalonic acid [1,2,2,6,6-pentamethyl-4-piperidinyl] ester, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino}], 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate, and the like. Trade names include: ADEKASTAB (registered trademark) LA series (LA-52, LA-57, LA-63P, LA-68, LA-72, LA-77Y, LA-81, LA-82, etc.) manufactured by ADEKA Co., Ltd.; TINUVIN (registered trademark) series (TINUVIN123, TINUVIN171, TINUVIN249, TINUVIN292, TINUVIN765, TINUVIN622SF, etc.) manufactured by BASF Japan Ltd.; Chimassorb (registered trademark) series (Chimassorb2020FDL, C Himassorb944FDL), etc.

[0164] The ratio of the additive in the solid content of the adhesive composition is, for example, 0.1 mass % or more and 1 mass % or less.

[0165] (Organic Solvent)

[0166] The adhesive composition may contain an organic solvent to adjust its viscosity. The organic solvent may contain at least one selected from the group consisting of tetrahydrofuran, diethyl ketone, tert-butyl alcohol, isopropyl alcohol, propylene glycol monomethyl ether, toluene, ethyl acetate, and cyclohexanone.

[0167] The ratio of the organic solvent in the solid content of the adhesive composition is, for example, 30 mass % or more and 80 mass % or less.

[0168] (Method for producing adhesive composition)

[0169] The adhesive composition can be obtained by, for example, the following first to fourth production methods.

[0170] The first method for producing an adhesive composition includes the following steps: a step of reacting a first polyfunctional active hydrogen compound with a first iso(thio)cyanate compound to obtain a first prepolymer; a step of reacting the first prepolymer with a second polyfunctional active hydrogen compound to obtain a second prepolymer; and a step of mixing the second prepolymer, a photochromic compound, and any additives.

[0171] The second method for manufacturing an adhesive composition includes the following steps: a step of reacting a first polyfunctional active hydrogen compound with a first iso(thio)cyanate compound to obtain a first prepolymer; a step of reacting the first prepolymer with a second polyfunctional active hydrogen compound to obtain a second prepolymer; a step of reacting the second prepolymer with a monofunctional active hydrogen compound to obtain a mixture of a first polymer and a second prepolymer; and a step of mixing the first polymer, the second prepolymer, a photochromic compound, and any additives.

[0172] The third method for manufacturing the adhesive composition includes the following steps: a step of reacting a first polyfunctional active hydrogen compound with a first iso(thio)cyanate compound to obtain a first prepolymer and a third prepolymer; a step of reacting the first prepolymer with a second polyfunctional active hydrogen compound to obtain a second prepolymer; a step of reacting the second prepolymer with a monofunctional active hydrogen compound to obtain a first polymer; and a step of mixing the first polymer, the third prepolymer, the photochromic compound and any additives.

[0173] The fourth method for manufacturing an adhesive composition includes the following steps: a step of reacting a first polyfunctional active hydrogen compound with a first iso(thio)cyanate compound to obtain a first prepolymer; a step of reacting the first prepolymer with a second polyfunctional active hydrogen compound to obtain a second prepolymer; a step of reacting the second prepolymer with a monofunctional active hydrogen compound to obtain a mixture of a first polymer, a second prepolymer and a fourth prepolymer; and a step of mixing the first polymer, the second prepolymer, the fourth prepolymer, a photochromic compound and any additives.

[0174] The reaction of the first multifunctional active hydrogen compound and the first iso(thio)cyanate compound is preferably carried out in the presence of an organic solvent. As the organic solvent, the above-mentioned ones can be used. The reaction is preferably carried out under a nitrogen atmosphere. In addition, the reaction is carried out, for example, at a reaction temperature of 60° C. or more and 150° C. or less for 3 hours or more and 10 hours or less. The reaction is preferably carried out until the end point is confirmed by the back titration method of the isocyanate group.

[0175] The reaction of the first prepolymer and the second multifunctional active hydrogen compound is preferably carried out in the presence of an organic solvent. As the organic solvent, the above-mentioned ones can be used. The reaction is preferably carried out in a nitrogen atmosphere. In addition, the reaction is carried out, for example, at a reaction temperature of 10° C. or more and 30° C. or less for 0.1 hour or more to 5 hours.

[0176] The reaction of the second prepolymer and the monofunctional active hydrogen compound is preferably carried out in the presence of an organic solvent. As the organic solvent, the above-mentioned ones can be used. The reaction is preferably carried out under a nitrogen atmosphere. In addition, the reaction is carried out, for example, at a reaction temperature of -10°C or more and 10°C or less for 0.1 hour or more and 5 hours or less.

[0177] <Coating>

[0178] The coating covers at least a portion of the surface of at least one of the first and second substrates. The coating preferably covers the surfaces of both the first and second substrates. The coating preferably covers the entire surface of the first and second substrates. If the coating covers a large area on the surface of the first and second substrates, there is a tendency to improve the adhesion with the optical element substrate and the shape stability of the laminate.

[0179] The thickness of the coating is, for example, 5 μm or more. If the thickness of the coating is thick, there is a tendency to improve the adhesion with the optical element substrate and the shape stability of the laminate. The thickness of the coating is preferably 10 μm or more, more preferably 20 μm or more, and further preferably 25 μm or more. On the other hand, if the thickness of the coating is too thick, there is a tendency to reduce the appearance of the laminate. The thickness of the coating is preferably 100 μm or less, more preferably 75 μm or less, and further preferably 50 μm or less.

[0180] The coating comprises at least one resin selected from the group consisting of epoxy resin, urethane resin and acrylic resin. The coating preferably comprises epoxy resin. The coating comprising epoxy resin has a tendency to have excellent appearance and higher adhesion to the optical element substrate. The type of resin contained in the coating can be confirmed by gas chromatography and Fourier transform infrared spectroscopy (FT-IR) analysis.

[0181] The surface of the coating layer preferably has at least one functional group selected from the group consisting of an acryloyl group, a methacryloyl group, and a vinyl group. If a coating layer having these functional groups on the surface is provided, there is a tendency that the adhesion with the optical element substrate is improved.

[0182] The presence of functional groups on the surface of the coating can be confirmed, for example, by Fourier transform infrared spectroscopy (FT-IR) analysis. That is, when there are acryloyl, methacryloyl, or vinyl groups on the surface, they will appear at 1600 cm in the IR spectrum. -1 Above and 1680cm -1Below and 790cm -1 Over 1000cm -1 Peaks were detected in the following range.

[0183] The coating layer can be formed, for example, by applying the coating layer-forming composition described below to the surface of at least one of the first and second substrates and curing the composition.

[0184] (Coating layer forming composition)

[0185] The coating layer-forming composition may include at least one resin selected from the group consisting of epoxy resins, urethane resins, and acrylic resins, and an organic solvent that dissolves or disperses these resins.

[0186] The organic solvent is, for example, at least one selected from the group consisting of methyl ethyl ketone, toluene, methanol, ethanol, n-propanol, isopropanol, acetone, phenol, diethyl ketone, and xylene.

[0187] The ratio of the resin in the coating layer-forming composition is, for example, 10 mass % to 50 mass % or less, and preferably 20 mass % to 30 mass % or less.

[0188] The coating layer-forming composition may further include a first compound having at least one polymerizable functional group selected from the group consisting of an acryloyl group, a methacryloyl group, a vinyl group, and an allyl group. If such a first compound is included, a coating layer having the above functional group on the surface can be obtained.

[0189] The first compound having a (meth)acryloyl group is, for example, a (meth)acrylate having one or more (meth)acryloyl groups. The first compound may be an acrylate, a methacrylate, or a mixture thereof. The first compound preferably has a methacryloyl group. The (meth)acrylate preferably further has at least one functional group selected from the group consisting of an epoxy group, an oxetane group, an isocyanate group (-N=C=O), an isothiocyanate group (-N=C=S), an amino group, a hydroxyl group, and a carboxylic acid group. If a monofunctional (meth)acrylate having such a functional group is used, there is a tendency for the adhesion of the coating to be improved.

[0190] Specific examples of (meth)acrylates include methacrylic acid, acrylic acid, methoxypolyethylene glycol methacrylate, methoxypolyethylene glycol methacrylate, methoxypolyethylene glycol acrylate, methoxypolyethylene glycol acrylate, stearyl methacrylate, lauryl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, octyl acrylate, lauryl acrylate, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, 3,4-epoxycyclohexylmethyl methacrylate, 3,4-epoxycyclohexylmethyl acrylate, and the like. In addition, compounds having an epoxy group represented by the following general formula (11) can also be mentioned.

[0191]

[0192] In the general formula (11), R 13 and R 14 are hydrogen atoms or methyl groups, respectively.

[0193] R 15 and R 16 Each is an alkylene group having 1 to 4 carbon atoms which may be substituted with a hydroxy group or a group represented by the following general formula (12).

[0194]

[0195] h and i are numbers from 0 to 20 respectively as average values.

[0196] Here, as R 15 and R 16 The alkylene group represented by may include, for example, methylene, ethylene, propylene, butylene, trimethylene, tetramethylene, etc. In addition, the compound represented by the above general formula (11) may be obtained in the form of a mixture of molecules having different molecular weights. Therefore, h and i are represented by average values.

[0197] Examples of the compound represented by the general formula (11) include glycidyl methacrylate, glycidyloxymethyl methacrylate, 2-glycidyloxyethyl methacrylate, 3-glycidyloxypropyl methacrylate, 4-glycidyloxybutyl methacrylate, polyethylene glycol glycidyl methacrylate having an average molecular weight of 406, polyethylene glycol glycidyl methacrylate having an average molecular weight of 538, polyethylene glycol glycidyl methacrylate having an average molecular weight of 1022, polypropylene glycol glycidyl methacrylate having an average molecular weight of 664, bisphenol A-monoglycidyl ether-methacrylate, methacrylic acid esters, and methacrylic acid esters. acrylate, 3-(glycidyl-2-oxyethoxy)-2-hydroxypropyl, glycidyl acrylate, glycidyloxymethyl acrylate, 2-glycidyloxyethyl acrylate, 3-glycidyloxypropyl acrylate, 4-glycidyloxybutyl acrylate, polyethylene glycol glycidyl acrylate with an average molecular weight of 406, polyethylene glycol glycidyl acrylate with an average molecular weight of 538, polyethylene glycol glycidyl acrylate with an average molecular weight of 1022, 3-(glycidyloxy-1-isopropoxy)-2-hydroxypropyl acrylate, 3-(glycidyloxy-2-hydroxypropoxy)-2-hydroxypropyl acrylate, and the like.

[0198] As the (meth)acrylate, at least one selected from the group consisting of glycidyl methacrylate, glycidyloxymethyl methacrylate, 2-glycidyloxyethyl methacrylate, 3-glycidyloxypropyl methacrylate, and glycidyl acrylate can be used.

[0199] The first compound having a vinyl or allyl group is, for example, a compound having at least one of more than one vinyl and allyl group. The compound preferably further has at least one functional group selected from the group consisting of an epoxy group, an oxetane group, an isocyanate group (-N=C=O), an isothiocyanate group (-N=C=S), an amino group, a hydroxyl group, and a carboxylic acid group. If a compound having such a functional group is used, there is a tendency for the adhesion of the coating to be improved.

[0200] Examples of the first compound having a vinyl group or an allyl group include methyl vinyl ketone, ethyl vinyl ketone, ethyl vinyl ether, styrene, vinyl cyclohexane, butadiene, 1,4-pentadiene, divinyl sulfide, divinyl sulfone, 1,2-divinylbenzene, 1,3-divinyl-1,1,3,3-tetramethyl-propanedisiloxane, diethylene glycol divinyl ether, divinyl adipate, divinyl sebacate, ethylene glycol divinyl ether, divinyl sulfoxide, and divinyl persulfide. persulfide), dimethyl divinylsilane, 1,2,4-trivinylcyclohexane, methyl trivinylsilane, N-vinylpyrrolidone, α-methylstyrene and α-methylstyrene dimer, (vinyloxy) methanol glycidyl ether, (vinyloxy) ethanol glycidyl ether, (vinyloxy) propanol glycidyl ether, (vinyloxy) butanol glycidyl ether, (vinyloxy) pentanol glycidyl ether, (vinyloxy) hexanol glycidyl ether, (vinyloxy) cyclohexanol glycidyl ether, (vinyloxy) cyclohexyl methanol glycidyl ether, (vinyloxymethyl) cyclohexanol glycidyl ether, (vinyloxymethyl) glycidyl ether, (vinyloxyethyl) cyclohexylmethanol glycidyl ether, (vinyloxyethyl) cyclohexanol glycidyl ether, (vinyloxyethyl) cyclohexylmethanol glycidyl ether, (vinyloxyethyl) cyclohexylethanol glycidyl ether, allyl glycidyl ether, vinyl glycidyl ether, o-vinylbenzyl glycidyl ether, m-vinylbenzyl glycidyl ether, p-vinylbenzyl glycidyl ether, 2-methyl-2-vinyloxirane, 3,4-epoxy-1-butene, 1,2-epoxy-5-hexene, 1,2-epoxy-9-decene, 1,2-epoxy-4-vinylcyclohexane, 4,4'-(propane-2,2-diyl)bis(2-allylphenol), and the like.

[0201] The first compound preferably comprises at least one selected from the group consisting of methacrylic acid, acrylic acid, glycidyl methacrylate (GMA), glycidyloxymethyl methacrylate, 2-glycidyloxyethyl methacrylate, 3-glycidyloxypropyl methacrylate, glycidyl acrylate, allyl glycidyl ether, vinyl glycidyl ether and 1,2-epoxy-4-vinylcyclohexane. In particular, glycidyl methacrylate is preferably added to a coating-forming composition comprising an epoxy resin. If such a composition is used, a coating having more excellent adhesion can be obtained.

[0202] In the coating forming composition, the proportion shared by the first compound is, for example, 0.05 mass % or more and 5 mass % or less, preferably 0.1 mass % or more and 1 mass % or less. The proportion shared by the first compound can be 1 mass % or more and 20 mass % or less, can be 3 mass % or more and 15 mass % or less, or can be 5 mass % or more and 10 mass % or less. If the proportion shared by the first compound is high, there is a tendency that the adhesion of the coating is improved. If the proportion shared by the first compound is low, there is a tendency that the appearance of the laminate is improved.

[0203] As the coating layer-forming composition, a commercially available adhesive or surface treatment agent can be used. As a commercially available adhesive, for example, ARON MIGHTY (registered trademark) series manufactured by Toagosei Co., Ltd. can be used.

[0204] <Support>

[0205] The laminate of the embodiment may further include a support. The support may be located between the adhesive layer and the first or second substrate, or between the first or second substrate and the coating. The support may further improve the shape stability of the laminate. The support may be colorless and transparent, white and transparent, or colored and transparent.

[0206] The support preferably contains at least one resin selected from the group consisting of polyethylene terephthalate, triacetyl cellulose, polyamide, a polycarbonate sheet, cellulose acetate butyrate, and (meth)acrylic acid.

[0207] The thickness of the support is preferably 50 μm or more, more preferably 100 μm or more, and further preferably 200 μm or more. If the thickness of the support is thick, there is a tendency for the strength of the laminate to be further improved. The upper limit of the thickness of the support is not particularly limited, and as an example, it is 1000 μm or less, and as another example, it can be 500 μm or less.

[0208] <Manufacturing method>

[0209] The method for manufacturing a laminate includes the following steps: applying the above-mentioned coating-forming composition to the main surface of at least one of the first substrate and the second substrate, and curing the coating film to provide a coating; applying the above-mentioned adhesive composition to the other main surface of the first substrate and the second substrate provided with the coating or the main surface of the first substrate and the second substrate not provided with the coating to obtain a coating; and laminating the second substrate on the coating film.

[0210] Hereinafter, the method for producing the laminate will be described in detail.

[0211] First, prepare the first and second substrates. As the first and second substrates, commercially available unstretched sheets of polypropylene alcohol resin can be used, or those subjected to stretching and dyeing treatments can be used. The first and second substrates can be subjected to surface treatments such as etching, alkali treatment, and corona treatment.

[0212] Then, a coating composition is applied on the main surface of one of the first substrate and the second substrate, for example, using a rod coater to form a coating film. The coating film is dried for more than 1 minute and less than 1 hour at a temperature of more than 40°C and 70°C. It should be noted that a coating film can be provided only on one of the first substrate and the second substrate. The dried coating film is cured by thermal polymerization to form a coating. For thermal polymerization, it can be performed before or after the adhesive composition is applied to the other main surface of the first substrate that is not provided with a coating. The coating can also be thermally polymerized simultaneously with the heat treatment described later. For the conditions of thermal polymerization, for example, it can be set to be performed at a temperature of more than 40°C and 160°C for more than 1 minute and less than 10 hours. If the heating temperature is set to an excessively high temperature, there will be concerns about the shrinkage of the first substrate and the second substrate.

[0213] Next, an adhesive composition is applied to the other main surface of the first substrate on which no coating is provided, for example, using a rod coater to form a coating film. The coating film is dried, for example, at a temperature of 60° C. or more and 150° C. for more than 1 minute and less than 1 hour. The second substrate is laminated in such a manner that it directly faces the dried coating film and the main surface of the second substrate on which no coating is provided is in contact with the coating film, for example, by laminating with a laminating roller to obtain a structure. It should be noted that the adhesive composition can be applied to a resin film such as polyethylene terephthalate, and the obtained coating film is cured to form an adhesive layer film. The adhesive layer is peeled off from the adhesive film, and the adhesive layer is clamped between the first and second substrates to obtain a structure.

[0214] Then, the obtained structure is subjected to a degassing treatment. During the degassing treatment, the structure is allowed to stand for 5 hours to 20 hours at a temperature of 40° C. to 80° C. under a vacuum of 500 Pa, for example. The degassing treatment can be performed in a temperature range of 30° C. to 60° C. under a vacuum of 15 Torr or less. The structure after the degassing treatment is subjected to a heat treatment.

[0215] It should be noted that the degassing treatment can be omitted. The structure in which the degassing treatment is omitted is subjected to a heat treatment. In addition, a humidification treatment can be performed instead of the degassing treatment. The humidification treatment can be performed, for example, at a temperature of 60° C. to 100° C. and in an environment of 40 RH% to 95 RH% for 0.1 hour to 10 hours. The structure after the humidification treatment is subjected to a heat treatment.

[0216] When the heat treatment is performed, the structure is heated at a temperature of 60° C. to 150° C. for 0.5 to 10 hours. When the adhesive composition comprises a first polymer and a second prepolymer or a third polymer, it is believed that a composite having an iso(thio)cyanate group can be formed by the heat treatment, thereby crosslinking with the first and second substrates. The heat-treated structure can be left to stand at room temperature for more than 1 week.

[0217] [Optical items]

[0218] The optical article of the embodiment includes the laminate of the embodiment. The optical article of the embodiment may include the laminate of the embodiment and an optical element substrate covering at least a portion of the coating. As the optical article, there can be listed: adhesive sheets, lenses, glasses, windows of houses and cars, liquid crystal displays, sun visors, clocks, etc. The lenses include semi-finished lenses and finished lenses.

[0219] Figure 2 This is a cross-sectional view schematically showing an example of the optical article according to the embodiment. Figure 2 The optical article 10 shown includes: a first optical element substrate 11, a second optical element substrate 12, and a stacked body 1 interposed therebetween. The optical article 10 has the shape of a concave-convex lens. The stacked body 1 has a curved surface along the shape of the lens. The first optical element substrate 11 is located on the concave side, and the second optical element substrate 12 is located on the convex side. The first optical element substrate 11 covers the entire surface of the first coating layer not shown in the figure of the stacked body 1. The second optical element substrate 12 covers the entire surface of the second coating layer not shown in the figure of the stacked body 1. The side surfaces of the stacked body 1 are not covered by the first and second optical element substrates. The side surfaces of the stacked body 1 may also be covered by the first and second optical element substrates.

[0220] Figure 3 It is a perspective view schematically showing an example of glasses according to the embodiment. Figure 3 The illustrated eyeglasses 100 include a lens 101 and a frame 102 that supports the lens 101. The lens 101 includes the optical article of the embodiment.

[0221] (Optical Component Substrate)

[0222] The optical element substrate may include a resin. The resin may include at least one selected from the group consisting of polyester resins, polyamide resins, allyl resins, acrylic resins, methacrylic resins, polyurethane resins, polyurethane urea resins, polythiocarbamate resins, polythiocarbamate urea resins, polythioepoxy resins, and polycarbonate resins.

[0223] The optical element substrate preferably contains an allyl resin. An allyl resin tends to have high adhesion to the coating layer of the laminate.

[0224] (Curable composition for forming an optical element substrate)

[0225] The curable composition for allyl resin contains an allyl monomer having an allyl group and a polymerization initiator. The allyl monomer contains, for example, at least one selected from the group consisting of diethylene glycol diallyl carbonate, diallyl isophthalate, and diallyl terephthalate. The polymerization initiator contains, for example, diisopropyl peroxycarbonate.

[0226] The curable composition for a (meth)acrylic resin contains a (meth)acrylic monomer having a (meth)acrylate group and a polymerization initiator.

[0227] The curable composition for urethane urea resin contains a prepolymer of a polyisocyanate compound and a polyol compound and a diamine compound. As the polyisocyanate compound, the polyol compound and the diamine compound, those described above in the adhesive composition can be used.

[0228] The curable composition for thiourethane resin contains a polyisocyanate compound, a polythiol compound and a polymerization catalyst. As the polyisocyanate compound, those described above in the adhesive composition can be used.

[0229] The curable composition for a thioepoxy-based resin contains a monomer having a thioepoxy group, a curing agent, and a polymerization catalyst.

[0230] (Method for manufacturing optical article)

[0231] The optical article of the embodiment can be produced, for example, by the following method.

[0232] First, prepare a casting mold and a gasket. The casting mold includes an upper mold and a lower mold. By combining the upper mold and the lower mold, a hollow portion can be formed inside. The gasket is arranged at the interface between the upper mold and the lower mold. A notch for fixing the laminate is provided on the inner side of the gasket. A convex portion or a concave portion can be provided on the inner side of the gasket instead of the notch. The casting mold and the gasket can use, for example, a known casting mold and gasket for molding plastic lenses.

[0233] The laminate can be subjected to shape processing such as bending in accordance with the shape of the casting mold. Specifically, the laminate is placed in a mold of a curved surface processing device. The mold has, for example, a lens shape such as a hemispherical shape. A hollow hole is provided on the bottom surface of the mold. A pressure regulating device such as a vacuum pump is connected to the hollow hole via a pipeline. The pressure regulating device is started to reduce the pressure in the space between the mold and the laminate. As a result, the second substrate of the laminate will deform and adhere to the bottom surface of the mold. At this time, in order to make the laminate easy to deform, the ambient temperature can be set to be above 70°C and below 160°C. After a specified time, the operation of the pressure regulating device is stopped, and the deformed laminate is taken out from the mold. The taken-out laminate is cooled, for example, at a temperature above 0°C and below 40°C. In this way, a curved surface processed laminate is obtained.

[0234] Next, the end of the laminate is inserted and fixed in the notch of the gasket. The gasket is set at the interface of the mold. Thus, the laminate is set to span the hollow part of the mold. Then, the hollow part of the mold is filled with a curable composition for forming an optical element substrate. The mold filled with the curable composition is heat-treated to cure the curable composition. When performing the heat treatment, for example, the temperature is gradually raised from room temperature to the curing temperature, and the curing temperature is maintained for a specified time after reaching the curing temperature. The curing temperature is, for example, above 60°C and below 100°C. The heating rate is, for example, above 1°C / hour and below 10°C / hour. The holding time at the curing temperature is, for example, above 1 hour and below 30 hours.

[0235] After the heat treatment is completed, the cured product is taken out from the mold. The cured product is further heated within a range of 60° C. to 150° C. for 1 hour to 10 hours. In this way, a laminated body can be obtained in which the coating surfaces on the first and second substrates of the laminated body are covered with the optical element substrate.

[0236] The optical article of the embodiment can be obtained by the following method. First, a part of the curable composition is filled in the lower mold of the above-mentioned casting mold. A laminate is arranged on the surface of the filled curable composition. Then, an upper mold is arranged in a manner opposite to the lower mold to form a hollow portion. The remaining curable composition is filled in the hollow portion. The obtained casting mold is heated using the same method as above to obtain a cured product. In this way, an optical article in which the entire main surface and side of the laminate are covered by the optical element substrate of the embodiment can be obtained.

[0237] In addition, the optical article of the embodiment can be obtained by the following method. First, a laminate is arranged along the upper surface of the mold. A curable composition is filled toward the surface of the mold of the laminate that is not in contact with the upper surface, i.e., the back side, and heated by the same method as above to obtain a first cured product. The first cured product is arranged in the mold. A curable composition is filled toward the surface of the laminate that is not covered by the cured product, and a second cured product is obtained by heat treatment under the same conditions as above. In this way, an optical article in which the main surface and any side of the laminate are covered by an optical element substrate can be obtained.

[0238] Example

[0239] The present invention is further described in detail by the following examples. These examples are only used to illustrate the present invention, but the spirit and scope of the present invention are not limited by these examples.

[0240] <Example 1>

[0241] Production of the first prepolymer FPP1

[0242] In a 2-liter reaction container, 100 g of the first isocyanate compound FI1, 315 g of the first polyfunctional active hydrogen compound FA1 and 40 g of the organic solvent OS1 are added to obtain a mixture. As the first isocyanate compound FI1, isophorone diisocyanate is used. As the first polyfunctional active hydrogen compound FA1, a polycarbonate diol with a number average molecular weight of 1000 is used. As the organic solvent OS1, diethyl ketone is used. The mixture is stirred at 150 rpm for 5 hours at 100° C. under a nitrogen atmosphere to obtain a reaction solution containing a first prepolymer. Hereinafter, the first prepolymer is also referred to as the first prepolymer FPP1. The end point of the reaction can be confirmed by the back titration method of the isocyanate group.

[0243] (Manufacturing of Second Prepolymer SPP1)

[0244] After adding 560 g of organic solvent OS1 and 150 g of organic solvent OS2 to a reaction liquid containing the first prepolymer FPP1 at 10°C, the liquid temperature was maintained at 15°C. As the organic solvent OS2, tert-butanol was used. 21.3 g of the second multifunctional active hydrogen compound SA1 was dropped into the reaction liquid and reacted at 15°C for 1 hour to obtain a reaction liquid containing the second prepolymer. As the second multifunctional active hydrogen compound SA1, bis(4-aminocyclohexyl)methane was used. Hereinafter, the second prepolymer is also referred to as the second prepolymer SPP1. It should be noted that in the reaction liquid containing the second prepolymer SPP1, the solid content concentration is 37.6% by mass.

[0245] The number average molecular weight of the second prepolymer SPP1 was measured and found to be 13000. The softening point was 98°C.

[0246] (Preparation of Adhesive Composition AC1)

[0247] 100 g of a reaction solution containing the second prepolymer SPP1, 1.02 g of a photochromic compound PC1, 0.34 g of ethylenebis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate] and 0.05 g of DOW CORNINGTORAY L-7001 were mixed and stirred at room temperature to obtain an adhesive composition. Hereinafter, this adhesive composition is also referred to as an adhesive composition AC1.

[0248] PC1: a compound represented by the following formula.

[0249]

[0250] (Production of Laminated Body OL1)

[0251] First, a 75 μm thick unstretched polyvinyl alcohol film was prepared as the first and second substrates. Hereinafter, this film is also referred to as the polyvinyl alcohol film PVF1.

[0252] A coating film is obtained by applying a coating resin composition to a main surface of a polyvinyl alcohol film PVF1 using a rod coater. The coating film is dried for 5 minutes at 60°C. In this way, a first substrate having a first coating film provided on a main surface is obtained. By the same method, a second substrate having a second coating film provided on a main surface is obtained. The thickness of the first and second coating films is 10 μm. As a coating composition, a solution obtained by dissolving an epoxy resin in a mixed solvent of toluene and methanol is used. Hereinafter, the coating composition is also referred to as a coating composition CF1.

[0253] Then, the adhesive composition AC1 is applied to a film made of PET (polyethylene terephthalate) (PUREX FILM manufactured by Teijin DuPont Film Co., Ltd., with a silicone coating) using a rod coater to obtain a third coating. After the third coating is dried at 100°C for 5 minutes, the PET film is peeled off to obtain a photochromic adhesive sheet with a thickness of about 30 μm. The photochromic adhesive sheet obtained is clamped between the main surface of the first substrate not provided with the first coating and the main surface of the second substrate not provided with the second coating, and they are bonded to obtain a structure. It should be noted that the structure is in the shape of a rectangular strip. One end of the structure in the long side direction is not coated with the adhesive composition and becomes an uncoated portion.

[0254] The structure was heated at 100° C. for 6 hours while its four corners were fixed so as not to shrink, thereby curing the first coating film, the second coating film, and the photochromic adhesive sheet. Hereinafter, this laminate is also referred to as a laminate OL1.

[0255] (Preparation of Curable Composition CC1)

[0256] 97 parts by mass of diethylene glycol diallyl carbonate and 3 parts by mass of diisopropyl peroxydicarbonate were mixed to obtain a curable composition. Hereinafter, this curable composition is also referred to as curable composition CC1.

[0257] (Curved Surface Processing of Laminated Body OL1)

[0258] First, the laminate OL1 was vacuum dried for 15 hours at 80°C and 13 Torr. The vacuum dried laminate OL1 was placed in a curved surface processing device and subjected to curved surface processing. Specifically, the obtained laminate was die-cut into 10 cm squares, and after being left to stand for 30 minutes at 45°C and 90% RH, it was processed into a spherical shape using a convex 6-curve (kabu) mold with a diameter of 83 mm. The processed sheet was dried to obtain a 6-curve sheet with a diameter of 83 mm.

[0259] (Manufacture of lens LS1)

[0260] The curved laminate OL1 is set in the notch on the inner side of the gasket. The gasket is set in the glass mold in such a way that the laminate OL1 is located in the hollow part. The glass mold is set as follows: the lens power D is 6.00, the lens diameter is 83mm, and the lens thickness is 7.5mm. The curable composition CC1 is injected into the hollow part of the glass mold. Using an air furnace, the glass mold after the curable composition CC1 is injected is slowly heated from 35°C to 85°C over 17 hours. After heating, the cured product is taken out from the gasket and the glass mold, and placed in a heating furnace at 90°C and heated for 3 hours. The periphery of the heated cured product is ground using a grinder to obtain a 70 mm diameter. Figure 2 The laminate shown in FIG. 1 is repeated to obtain a total of 3 lenses. Hereinafter, this lens is also referred to as lens LS1.

[0261] <Example 2>

[0262] A lens was obtained in the same manner as in Example 1 except that the thickness of the coating layer was changed to 25 μm.

[0263] <Example 3>

[0264] A lens was obtained in the same manner as in Example 1 except that the coating layer-forming composition CF2 was used as the coating layer-forming composition. The coating layer-forming composition CF2 was prepared by mixing the coating layer-forming composition CF1 with glycidyl methacrylate (GMA). The amount of GMA in the coating layer-forming composition CF2 was 2% by mass.

[0265] <Examples 4 to 6>

[0266] Lenses were obtained in the same manner as in Example 3 except that the thickness of the coating layer was changed to 25 μm, 50 μm, and 75 μm, respectively.

[0267] <Example 7>

[0268] A lens was obtained in the same manner as in Example 2 except that the coating layer-forming composition CF3 was used as the coating layer-forming composition. The coating layer-forming composition CF3 was a solution prepared by dissolving a urethane resin in methyl ethyl ketone.

[0269] <Example 8>

[0270] A lens was obtained in the same manner as in Example 5 except that the coating layer-forming composition CF4 was used as the coating layer-forming composition. The coating layer-forming composition CF4 was prepared by mixing the coating layer-forming composition CF1 with allyl glycidyl ether. The amount of allyl glycidyl ether in the coating layer-forming composition CF4 was 10% by mass.

[0271] <Example 9>

[0272] A lens was obtained in the same manner as in Example 5 except that the coating layer-forming composition CF5 was used as the coating layer-forming composition. The coating layer-forming composition CF5 was prepared by mixing the coating layer-forming composition CF1 with 1,2-epoxy-4-vinylcyclohexane. The amount of 1,2-epoxy-4-vinylcyclohexane in the coating layer-forming composition CF5 was 5% by mass.

[0273] <Example 10>

[0274] A 60 μm thick triacetyl cellulose (hereinafter, the film will also be referred to as film TAC1) was prepared instead of PVA1. Furthermore, after obtaining the structure, instead of curing the first coating film, the second coating film and the photochromic adhesive sheet by heating at 100°C for 6 hours while fixing the four corners without shrinking them, the laminate was obtained by degassing at 40°C and 13 Torr for 16 hours and then curing them by heating at 100°C for 6 hours. Except for this, the lens was obtained by the same method as Example 8.

[0275] <Example 11>

[0276] A lens was obtained by the same method as in Example 10 except that the coating layer-forming composition CF5 was used as the coating layer-forming composition.

[0277] <Example 12>

[0278] A lens was obtained in the same manner as in Example 10 except that the coating layer-forming composition CF6 was used as the coating layer-forming composition. The coating layer-forming composition CF6 was prepared by mixing the coating layer-forming composition CF1 with methacrylic acid. The amount of methacrylic acid in the coating layer-forming composition CF6 was 20% by mass.

[0279] <Comparative Example 1>

[0280] A lens was obtained in the same manner as in Example 2 except that the formation of the coating layer was omitted.

[0281] <Comparative Example 2>

[0282] A lens was obtained in the same manner as in Example 10 except that the formation of the coating layer was omitted.

[0283] <Evaluation Test>

[0284] (FT-IR analysis of coating)

[0285] The functional groups on the surface of the coating layer of the obtained laminate were confirmed using FT-IR. The results are shown in Table 1.

[0286] (Measurement of Photochromic Properties of Laminated Body and Lens)

[0287] The maximum absorption wavelength, color concentration, and fading speed of the obtained laminate were measured.

[0288] Specifically, first, at a temperature of 23°C, one substrate side of the laminate was irradiated for 120 seconds with a xenon lamp L-2480 (300W) SHL-100 manufactured by Hamamatsu Photonics Co., Ltd. through an air filter (manufactured by Corning) to color the photochromic compound. The beam intensity was set to 365nm = 2.4mW / cm 2 , 245nm=24μW / cm 2 .

[0289] The maximum absorption wavelength (λmax) after color development was determined using a spectrophotometer (Multi-Channel Optical Detector MCPD1000) manufactured by Otsuka Electronics Co., Ltd.

[0290] The absorbance ε(0) of the maximum absorption wavelength of the laminated body when not irradiated with the xenon lamp is measured. Then, the laminated body is irradiated with the xenon lamp using the above-mentioned beam intensity for 120 seconds, and the absorbance ε(120) of the maximum absorption wavelength of the laminated body is measured. The value obtained by subtracting ε(0) from the absorbance ε(120) is set as the color development concentration. The higher this value is, the better the photochromic property can be said to be.

[0291] The time required for the color density to decrease to 1 / 2 was measured and defined as the fading speed (t1 / 2 (seconds)). The shorter this time is, the better the photochromic property is.

[0292] In all the laminates and lenses of Examples and Comparative Examples, the color development density was 1.1 and the fading speed was 40 seconds.

[0293] (Appearance Evaluation of Laminated Body (Appearance))

[0294] The appearance of the laminate was evaluated by the following method. Specifically, turbidity was confirmed by visual evaluation, using LIQCX75 manufactured by Bulbtronics, and visually observing the image projected on the lens using an ozone-free xenon arc lamp. The evaluation criteria are as follows. The results are shown in Table 1.

[0295] 1. There is no white turbidity in visual evaluation, and 0 to 2 lines can be confirmed in the image projected on the lens using an ozone-free xenon arc lamp.

[0296] 2. There is no white turbidity in visual evaluation, and 3 to 5 lines can be confirmed in the image projected on the lens using an ozone-free xenon arc lamp.

[0297] 3. There is no white turbidity in visual evaluation, and 6 or more lines can be confirmed in the image projected on the lens using an ozone-free xenon arc lamp.

[0298] 4. White turbidity in visual evaluation.

[0299] (Evaluation of shape stability of laminated body)

[0300] The shape stability of the laminate was evaluated by the following method. First, a laminate with curved surface processing was prepared by the same method as described in Example 1. The laminate was placed in a thermostatic bath at 25°C and a relative humidity of 60% RH. The laminate was taken out of the thermostatic bath every 30 minutes and then installed in a mold to visually confirm whether there was any shape change. The time until it was confirmed that the shape change occurred due to the inability to be consistent with the mold was measured. The same test was carried out in an environment of 40°C and a relative humidity of 35% RH and in an environment of 5°C and a relative humidity of 90% RH. The results are shown in Table 1.

[0301] (Evaluation of the close fit of the lens)

[0302] The adhesion of the laminate and the optical element substrate in the obtained lens was evaluated by the following method. First, the interface between the laminate and the optical element substrate was pressed with a superhard blade scraper to confirm whether peeling could be found. Then, after the lens was boiled in distilled water for a test time, the interface between the laminate and the optical element substrate was pressed with a superhard blade scraper to confirm whether peeling could be found. The evaluation criteria are as follows. The results are shown in Table 1.

[0303] 1. Before the boiling test, peeling was observed between the laminate and the optical element substrate.

[0304] 2. After 3 hours of boiling test, peeling was observed between the laminate and the optical element substrate.

[0305] 3. No peeling was found between the layers.

[0306] [Table 1]

[0307]

[0308] As shown in Table 1, the shape stability and lens adhesion of the laminated bodies of Examples 1 to 12 provided with the coating layers were superior to those of the laminated bodies of Comparative Examples 1 to 2 not provided with the coating layers.

[0309] The preferred embodiments of the present invention are described below.

[0310] [1] A laminate comprising:

[0311] A first substrate and a second substrate, wherein the first substrate and the second substrate comprise polyvinyl alcohol resin or cellulose resin;

[0312] an adhesive layer interposed between the first substrate and the second substrate to bond them together; and

[0313] The coating layer covers at least a portion of a surface of at least one of the first substrate and the second substrate, and includes at least one resin selected from the group consisting of epoxy resins, urethane resins, and acrylic resins.

[0314] [2] The laminate according to [1], wherein the coating layer has a thickness of 5 μm to 50 μm.

[0315] [3] The laminate according to [1] or [2], wherein the coating layer contains an epoxy resin.

[0316] [4] The laminate according to any one of [1] to [3], wherein the coating layer has at least one functional group selected from the group consisting of an acryloyl group, a methacryloyl group, a vinyl group, and an allyl group on the surface.

[0317] [5] A laminate according to any one of [1] to [4], wherein the coating layer comprises a cured product of a coating layer-forming composition, the coating layer-forming composition comprising a resin and an organic solvent, the resin being selected from at least one of the group consisting of an epoxy resin, a urethane resin and an acrylic resin.

[0318] [6] The laminate according to [5], wherein the coating layer-forming composition further comprises a first compound having at least one polymerizable functional group selected from the group consisting of an acryloyl group, a methacryloyl group, a vinyl group, and an allyl group.

[0319] [7] The laminate according to [5] or [6], wherein the first compound further comprises at least one functional group selected from the group consisting of an epoxy group, an oxetane group, an isocyanate group, an isothiocyanate group, an amino group, a hydroxyl group, and a carboxylic acid group.

[0320] [8] The laminate according to [6] or [7], wherein the first compound comprises at least one selected from the group consisting of methacrylic acid, acrylic acid, glycidyl methacrylate, glycidyloxymethyl methacrylate, 2-glycidyloxyethyl methacrylate, 3-glycidyloxypropyl methacrylate, glycidyl acrylate, allyl glycidyl ether, vinyl glycidyl ether and 1,2-epoxy-4-vinylcyclohexane.

[0321] [9] The laminate according to any one of [1] to [8], wherein the adhesive layer contains a functional dye.

[0322]

[10] The laminate according to any one of [1] to [9], wherein the adhesive layer contains a photochromic compound.

[0323]

[11] An optical article comprising the laminate according to any one of [1] to

[10] .

[0324]

[12] An optical article comprising:

[0325] The laminated body described in any one of [1] to

[10] ; and

[0326] An optical element substrate, which is covered with at least a portion of the aforementioned coating.

[0327]

[13] The optical article according to

[12] , wherein the optical element substrate comprises an allyl resin.

[0328]

[14] A lens comprising the optical article according to any one of

[11] to

[13] .

[0329]

[15] A pair of glasses comprising the lens described in

[14] .

Claims

1. A laminate comprising: A first substrate and a second substrate, wherein the first substrate and the second substrate comprise polyvinyl alcohol resin or cellulose resin; an adhesive layer interposed between the first substrate and the second substrate to bond them together; and The coating layer covers at least a portion of a surface of at least one of the first substrate and the second substrate, and includes at least one resin selected from the group consisting of epoxy resins, urethane resins, and acrylic resins.

2. The laminate according to claim 1, wherein The coating layer has a thickness of 5 μm or more and 50 μm or less.

3. The laminate according to claim 1, wherein The coating comprises an epoxy resin.

4. The laminate according to claim 1, wherein The coating layer has at least one functional group selected from the group consisting of an acryloyl group, a methacryloyl group, a vinyl group, and an allyl group on the surface.

5. The laminate according to claim 1, wherein The coating layer includes a cured product of a coating layer-forming composition, wherein the coating layer-forming composition includes a resin and an organic solvent, and the resin is at least one selected from the group consisting of epoxy resins, urethane resins, and acrylic resins.

6. The laminate according to claim 5, wherein The coating layer-forming composition further includes a first compound having at least one polymerizable functional group selected from the group consisting of an acryloyl group, a methacryloyl group, a vinyl group, and an allyl group.

7. The laminate according to claim 6, wherein: The first compound further includes at least one functional group selected from the group consisting of an epoxy group, an oxetane group, an isocyanate group, an isothiocyanate group, an amino group, a hydroxyl group, and a carboxylic acid group.

8. The laminate according to claim 6, wherein: The first compound includes at least one selected from the group consisting of methacrylic acid, acrylic acid, glycidyl methacrylate, glycidyloxymethyl methacrylate, 2-glycidyloxyethyl methacrylate, 3-glycidyloxypropyl methacrylate, glycidyl acrylate, allyl glycidyl ether, vinyl glycidyl ether and 1,2-epoxy-4-vinylcyclohexane.

9. The laminate according to claim 1, wherein The adhesive layer contains functional pigments.

10. The laminate according to claim 1, wherein The bonding layer includes a photochromic compound. An optical article comprising the laminate according to claim 1 .

12. An optical article comprising: The laminate according to claim 1; and An optical element substrate covers at least a portion of the coating.

13. The optical article according to claim 12, wherein: The optical element substrate includes an allyl resin.

14. A lens comprising the optical article according to claim 11.

15. Spectacles comprising the lens according to claim 14.

Citation Information

Patent Citations

  • Polarizing lens and method for manufacturing a polarizing lens

    JP2011501235A

  • Photochromic curable composition

    WO2015005391A1

  • Functional multilayer body and functional lens using functional multilayer body

    WO2019163728A1